FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI E-MONEY (Studi Pada Kartu BRIZZI BRI Cabang Cik Di Tiro Yogyakarta) - , EKA PURWIATI; , Gunawan wibisono, SE, M.Acc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to examine the effect of the Factors Affecting the Adoption of emoney (Studies on Brizzi Card BRI branch Cik Di Tiro yogyakarta). Purposive sampling method used in the selection of data samples and obtained a sample of 435 people who are users and non-users of e-money card from the bank BRI Brizzi. Statistical tool used is the SEM analysis. Data were analyzed using Amos software. The results of this study indicate that the variables that influence the adoption of e-money consisting of variable security and Privacy, perceived of usefulness, perceived ease of use, perceived enjoyment, trus, information on emoney, and attitude toward are factors that positively influence the intention of using e-money.